Pengembangan Buku Pedoman Pendidikan Karakter untuk Penanggulangan Kenakalan Siswa - Andres Andres; Sri Utaminingsih; Erik Aditia Ismaya (Peneliti.net, 2022)
This study aims to determine the need for developing character education guidebooks for overcoming student delinquency at SMP Negeri 1 Tahunan, knowing the process of developing character education guidebooks, obtaining the validity and feasibility of developing character education guidebooks for overcoming student delinquency in SMP Negeri 1 Tahunan, and to find out the effectiveness of developing character education guidebooks for the prevention of student delinquency in 1 yearly SMP Negeri 1 Tahun. This research is a development research or Research and Development (R&D) using the Borg and Gall development method which aims to develop a character education guidebook for overcoming student delinquency at SMP Negeri 1 Tahunan. Data was collected using observation, interview and questionnaire techniques. The data were then analyzed qualitatively and quantitatively. Qualitative data analysis to analyze the responses of principals and teachers to the use of character education manuals for overcoming student delinquency. Meanwhile, quantitative data analysis was used to analyze the data collected from the questionnaire. The results of the study 1) Character education for dealing with student delinquency at SMP Negeri 1 Tahunan is carried out through classroom learning, habituation, application of manners, rules and other ways that are carried out in a non-programmed manner. However, there is a lack of manuals that regulate the mechanism and steps for implementation, so a media guide is needed. 2) The process of developing a character education guidebook for preventing delinquency at SMP Negeri 1 Tahunan students begins with the preparation of a character education design, which is then made in the form of a book media. By utilizing literature studies and listening to input from various school stakeholders. 3) The development of the character education guidebook passed expert validation tests, both media, strategy and material experts and the results showed that the developed guidebook was valid and feasible to use with some notes of improvement. 4) The character education guidebook for overcoming student delinquency at SMP Negeri 1 Tahunan is declared effective, it can be used, it is known based on the questionnaire distributed and then analyzed as a whole in the good category. In the media aspect, the mean value of 18.39 is included in the 18-19 interval on good criteria. in the material aspect, the mean value of 17.21 is included in the interval 17-18 on good criteria. In the strategic aspect, the mean value of 17.63 is included in the interval 17-18 on good criteria. Keywords: Guidebook, Character Education, Student Delinquency